Socio-Psychological Features of the Values of Modern Adolescents - Amirova Luiza Maratovna (European Science Publishing, 2023)
This article explores the socio-psychological features shaping the values of modern adolescents. Drawing on a comprehensive literature analysis, the study investigates the factors influencing the value systems of today's youth. Employing both quantitative and qualitative research methods, the results reveal noteworthy patterns and trends in adolescent values. The discussion section delves into the implications of these findings, offering insights into the socio-psychological dynamics that underpin the value formation process. The article concludes with actionable suggestions for parents, educators, and policymakers to foster positive value development among adolescents.
Keywords: Adolescents, values, socio-psychological, modern, development, influences.